Certain Physiological Studies on the Indian Elephants - Sreekumar K P (Department of Physiology and Biochemistry, College of Veterinary and Animal Sciences, 1986)
Clinically healthy 44 Indian elephants, of varying ages and both sexes, maintained under ideal conditions of management formed the subjects for the study. Prediction equations to estimate body weight and height at shoulder from linear measurements had been derived. True body surface area in elephants was measured. Formulae for computation of total body surface area from areas of individual regions of the body and from body weight and height had been presented and its usefulness discussed. Normal values for haematological parameters viz., specific gravity, viscosity, icterus index, pH, coagulation time and erythrocyte sedimentation rates had been established. At 15 minutes, 50 per cent of erythrocytes had settled. Use of erythrocyte sedimentation rate as a clinical test is discussed. Elephants had low albumin and high globulin levels and the A/G ratio was less than one. The electrophoretic fractionation of total proteins and lipoproteins have been discussed. Polymorphism in albumin was observed but no variant of haemoglobin could be detected. Levels of glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, lactic dehydrogenase and creatine phosphokinase have been assayed. The mineral status of elephants had been established. Normal levels of sodium, potassium, calcium, magnesium, iron, copper and zinc as well as the iron: copper ratio had been worked out.